P11.27 Does accessing non-occupational post exposure prophylaxis and the associated clinical experience impact condom use among men who have sex with men in victoria, australia. (13th September 2015) - Wilkinson, Anna L; Pierce, Anna B; El-Hayek, Carol; McCarthy, Damien; Armishaw, Jude; Watson, Kerrie; Price, Brian; Wright, Edwina; Fairley, Christopher; Leslie, David; Roth, Norm; Tee, BK; et al.
Abstract : Background: Condom promotion is a key component of combination HIV prevention globally. There is evidence from clinical settings that intense interventions successfully increase condom use. However it is unknown if routine sexual health clinical encounters, including encounters potentially prompted by concern relating to particularly high risk events, have the same impact on reducing HIV risk behaviours. We compared self-reported condom use among MSM before and after receiving standard care non-post exposure prophylaxis. Methods: Data from MSM accessing the Victorian NPEP Service (VNPEPS) was linked to HIV/STI testing data from Victorian Primary Care Network for sentinel surveillance (VPCNSS) clinics between 2007–2013. Analysis included data from MSM who accessed NPEP and reported condom use at their most recent HIV/STI test prior to NPEP (baseline) and two tests following NPEP (follow-up one and two). Only the first NPEP episode was included. Proportion of MSM reporting inconsistent condom use at baseline (test immediately prior to NPEP) and follow-up one and two were compared using a two sample test of proportions. Results: Among 1199 MSM presenting for NPEP on 2094 occasions, 6329 test and risk behaviour records were obtained from VPCNSS sites pre-and post-NPEP. A total of 303 MSM had data on condom use at baseline and two follow ups. Inconsistent condom use was reported by 146 (48.2%) of MSM at baseline, 138 (45.5%) at follow-up one (p = 0.60) and 146 (48.2%) at follow-up two (p = 1.0). Follow-up two occurred a median of 15 months (IQR = 10–23) after NPEP presentation. Conclusion: In this study we found no change in condom use following NPEP among MSM with pre- and post-NPEP VPCNSS testing histories. Though generalisability to all MSM is limited, this analysis offers insight into a key risk population and highlights the potential need for tailored strategies to promote primary prevention during risk event-prompted clinical presentations. Disclosure of interest statement: The Victorian Department of Health funds the VNPEPS and ongoing surveillance projects within the Burnet Institute. The authors would like to acknowledge the NHMRC who provide funding to Margaret Hellard as a Senior Research Fellow, Mark Stoové as a Career Development Fellow and Anna Wilkinson as a public health scholarship recipient. Edwina Wright receives funding from a research grant from NIH, research funding from the Victorian Department of Health and unrestricted research funds from Gilead, Abbott, Janssen Cilag, MSD and Boehringer Ingelheim. She has also received funding that has been used for research purposes only from ViiV, Merck, Gilead, and Abbott for consultancy work, payment for lectures from ViiV and payment for developing educational resources for ViiV, MSD and Gilead. The study drug for the VicPrEP study has been donated by Gilead Sciences. The authors gratefully acknowledge the contribution to this work of Victorian Operational Infrastructure Support Program received by the Burnet Institute.